Overcoming impossible : learn to lead, build a team, and catapult your business to success - Irvine, Robert, 1965-; Tuthill, Matt (HarperCollins Leadership, an imprint of HarperCollins Focus LLC, 2023)
Make achieving your goals and finding success possible with this one-of-a-kind guide by Robert Irvine, popular host of Food Network's Restaurant: Impossible.